THE ANALYSIS OF ENGLISH LECTURERS’ TEACHING MODELS AT ENGLISH EDUCATION DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF NORTH MALUKU TERNATE - Mahmud, Adi F; Rahman, Andi Qashas (ELT Worldwide: Journal of English Language Teaching, 2015)
To achieve the teaching goals well, the teachers or lecturers are demanded to master all teaching components. One of the components is teaching model. Teaching model can drive the teachers or lecturers to achieve teaching goals well. This research attempted to find out (i) the English lecturers’ teaching models applied in teaching in the classroom, (ii) the English lecturers’ reasons for applying those teaching models, and (iii) the English students’ perceptions of the English lecturers’ teaching models applied. Data were collected by classroom observation and semi-structure interview. Then, data were analyzed by employing descriptive qualitative method. The participants consisted of five English lecturers and students. The findings of the research showed that (i) Most of the respondents in this research did not apply innovative teaching models. Most of the teaching models applied by respondents were still conventional. (ii) There were some respondents who applied group discussions and presentation, but the sequences of teaching that were applied did not characterize an innovative teaching model, (iii) The respondent 4 applied innovative teaching models twice in two meetings. However, he also applied conventional teaching models. Then, all respondents’ teaching models did not involve a new teaching model or method in teaching interaction in the classroom, (iv) Lecturing is one of the dominances teaching models used by all respondents in teaching in the classroom, (v) There were some reasons underpinning all respondents in choosing a teaching model to be applied. The reasons included the students’ proficiency, the instructional material, students’ understanding, the easiness, simple, and teaching goals. Further, all respondents considered that those teaching models were appropriate and effective to be applied in teaching and learning interaction, and (v) Not all respondents’ reasons in line with the five students’ perceptions. All students’ perceptions showed that some teaching models used by respondents were boring and uninteresting. Key Words: analysis, teaching models, English lecturers